Use of endoscopic ultrasound for pancreatic cancer from 2000 to 2016 - Rustgi, Sheila D.; Zylberberg, Haley M.; Amin, Sunil; Aronson, Anne; Nagula, Satish; DiMaio, Christopher J.; Kumta, Nikhil A.; Lucas, Aimee L. (Endoscopy International Open, 2022)
Background and study aims Pancreatic cancer (PC) is the fourth most common cause of cancer death in the United States. Previous studies have suggested a survival benefit for endoscopic ultrasound (EUS), an important tool for diagnosis and staging of PC. This study aims to describe EUS use over time and identify factors associated with EUS use and its impact on survival.Patients and methods This was a retrospective review of the Surveillance, Epidemiology and End Results (SEER) database linked with Medicare claims. EUS use, clinical and demographic characteristics were evaluated. Chi-squared analysis, Cochran-Armitage test for trend, and logistic regression were used to identify associations between sociodemographic and clinical factors and EUS. Kaplan-Meier and Cox proportional hazard ratios were used for survival analysis.Results EUS use rose during the time period, from 7.4 % of patients in 2000 to 32.4 % in 2015. Patient diversity increased, with a rising share of older, non-White patients with higher Charlson comorbidity scores. Both clinical (receipt of other therapies, PC stage) and nonclinical factors (region of country, year of diagnosis) were associated with receipt of EUS. While EUS was associated with a survival improvement early in the study period, this effect did not persist for PC patients diagnosed in 2012 to 2015 (median survival 3 month ± standard deviation [SD] 9.8 months without vs. 4 months ± SD 8 months with EUS). Conclusions Our data support previous studies, which suggest a survival benefit for EUS when it was infrequently used, but finds that benefit was attenuated as EUS became more widely available.